2021
DOI: 10.1057/s41287-021-00361-9
|View full text |Cite
|
Sign up to set email alerts
|

What’s the Story on Agriculture? Using Narratives to Understand Farming Households’ Aspirations in Meru, Kenya

Abstract: In the limited research on farming aspirations, little attention has been paid to the narratives which frame and shape them, and the ways in which the aspirations of those who farm intersect with the goals of extension services. Drawing on multimethod research conducted in Meru County, Kenya, we demonstrate how aspirations are not only situated within a consideration of personal circumstances, but are shaped in crucial ways by networks of relations and by the perceived possibilities afforded by material and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…In addition to the contextual conditions and the adjacent possible that shape the options people can pursue, human behaviour and the resulting limitation of information processing and choice-making (World Bank 2015) shape aspiration formation and the 'aspiration window'. The aspiration window (here dark grey) can be described as imaginable futures based on observations of peers and evolves through social interactions (Appadurai 2004;Dilley et al 2021;Ray 2006) and through this interaction it can change or widen (Macours and Vakis 2014). The aspiration window does not necessarily align with real options as biases and imagination influence its size and shapes "what individuals perceive as desirable, possible, or even 'thinkable' for their lives" (World 1 Therefore, we do not explicitly focus on any distinct pathway or strategy but aim to capture any strategy be it agriculture, off-farm employment or self-employed businesses.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the contextual conditions and the adjacent possible that shape the options people can pursue, human behaviour and the resulting limitation of information processing and choice-making (World Bank 2015) shape aspiration formation and the 'aspiration window'. The aspiration window (here dark grey) can be described as imaginable futures based on observations of peers and evolves through social interactions (Appadurai 2004;Dilley et al 2021;Ray 2006) and through this interaction it can change or widen (Macours and Vakis 2014). The aspiration window does not necessarily align with real options as biases and imagination influence its size and shapes "what individuals perceive as desirable, possible, or even 'thinkable' for their lives" (World 1 Therefore, we do not explicitly focus on any distinct pathway or strategy but aim to capture any strategy be it agriculture, off-farm employment or self-employed businesses.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Previous research has shown that Kenyan farmers' choices are driven by income but only as a means of achieving deeply held life goals (Okello et al 2019) and framed and embedded in context and social dynamics (Dilley et al 2021). Exploring these broader and less tangible factors that influence aspirations, people were asked to balance what they identify most with across 'where they live', 'what they do' and 'their role in the community'.…”
Section: Framing Aspirationsmentioning
confidence: 99%
“…Here we assume that political decisions that work in line with local aspirations would ultimately be more successful for both local individual progress as well as for political success as measured in votes. Therefore, in this Special Issue, aspirations are not purely seen as "an individual preference, rather aspirations are understood as social in nature in that they are embedded and shaped by the materiality, practices, discourses and beliefs of a culture" (Dilley et al 2021). Within this context, the "thick of social life" (Appadurai 2004, p. 67) applies just as well to politicians and development actors as it does to individual decision makers.…”
Section: Conceptual Approachmentioning
confidence: 99%
“…Local political processes and international organizations are setting future visions based on their assessments and values while a collection of individual aspirations is shaping the response to these through the multitude of visions for future lives. Linking and aligning these two views and processes could significantly improve outcomes and accelerate progress (Neely et al 2021;Dilley et al 2021). How this plays out towards reaching development goals such as livelihood improvement or environmental targets is outlined and reflected upon in more detail in the following section.…”
Section: Conceptual Approachmentioning
confidence: 99%
See 1 more Smart Citation